Self-healing polymers and polymer composites - Zhang, Ming Qiu.; Rong, Min Zhi.; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
"This book covers the fundamentals, theory, design, fabrication, characterization, and application of self-healing polymers and polymer composites. Innovative routes that correlate materials chemistry to the self-healing functionality are summarized for future industrial use. Throughout the book, the authors emphasize integration of existing techniques and / or novel synthetic approaches for target-oriented materials design and fabrication. With this book, experienced readers will gain a comprehensive view of the emerging field, while new researchers will understand the framework for creating new materials or new applications"--
"This book covers the fundamentals, theory, design, fabrication, characterization, and application of self-healing polymers and polymer composites"--
Frontmatter -- Color Plates -- Basics of Self-Healing: State of the Art -- Theoretical Consideration and Modeling -- Extrinsic Self-Healing via Addition Polymerization -- Extrinsic Self-Healing via Cationic Polymerization -- Extrinsic Self-Healing via Anionic Polymerization -- Extrinsic Self-Healing via Miscellaneous Reactions -- Intrinsic Self-Healing via Diels-Alder Reaction -- Applications -- Appendix -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Polymeric composites; Self-healing materials; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Polymeric composites; Self-healing materials; Electronic books; Electronic resource